Becoming women: Gender and religion/culture in novels by Nawal El Saadawi and Gabriel García Márquez - Abd Rabouh, Sherin Hany (AUC Knowledge Fountain, 2018)
This study examines male characters' subjugation of women through religious discourse as a validating institution. Two third world writers' works, Nawal El Saadawi's The Fall of the Imam and Gabriel García Márquez Chronicle of a Death Foretold, explore this subjugation through the social construction of religion, resulting in the preservation of "discourses" such as religion over the years. I use Simone de Beauvoir and Edward Said's theories in my study of how women came to be identified with inferiority while men came to be identified with superiority. Beauvoir's theory addresses women and men directly, focusing on how societies shape women, classifying them as the "second sex" and men as the first and superior sex. Said addresses the feminized Orient, where his political discussions of the Occident-Orient relationship bring out how the stereotypical image of the inferior Orient came to be. In addition, I refer to Michel Foucault's concept of "discourse" to help in reaching the roots of the embeddedness and solid position of social constructions and their upholding through knowledge and history, along with Giambattista Vico's notion of history, too. El Saadawi focuses on presenting religion as a daily tool that governs the community while García Márquez uses religion as a tool to promote the entrenched cultural traditions that the community has no choice but to abide by. The study aims to present the ongoing error of attempting to gain equality between both genders when there should be an acceptance of the differing roles, however, without hindering the progress or success of any of the two genders.